Enantio-Enriched CPL-active helicene–bipyridine–rhenium complexes1. Issue 18 (4th March 2015) - Saleh, Nidal; Srebro, Monika; Reynaldo, Thibault; Vanthuyne, Nicolas; Toupet, Loïc; Chang, Victoria Y.; Muller, Gilles; Williams, J. A. Gareth; Roussel, Christian; Autschbach, Jochen; Crassous, Jeanne
<x xml:space="preserve">Abstract</x> Incorporation of a rhenium atom within an extended helical π-conjugated bi-pyridine system leads to the first examples of rhenium-based phosphors that exhibit circularly polarized luminescence.